Quick change ! - Johnson, Margaret (United Kingdom Cambridge University Press, 2010)
It's Helen birthday and she's happy. But then everything changes. And Helen learns who she really is.
Cambridge Experience Readers, previously known as Cambridge Discovery Readers, is an exciting series of original fiction, adapted fiction and factbooks, specifically written for pre-teen and teenage learners of English.
Contents.
Keywords: Language Learning; Starter/Beginner level; Reading books; Fantasy